Bérénice, poésie pure ou tragédie pure ? - Laurent Thirouin (Etudes Epistémè)
Bérénice is often presented as a lyric poem in five acts and thus only marginally complying to the requirements of the tragedy. It is the simplest of Racine's tragedies, provocatively simple and claimed to be so by the author. Henri Bremond, in his Racine et Valéry (1930), identifies in this play the markers of "pure poetry" and he considers Racine’s works to be particularly representative of the genre. But such a feeling rests on a questionable idea of ​​the tragic genre. If Bérénice is a borderline tragedy, it is not because it evades the requirements of tragedy and takes on a poetic form, but because it pushes to the limit the very demands of tragedy. The key components of the classical tragedy are present in this play by Racine in an almost exemplary form. This article dismisses three misconceptions about tragedy in general, and classical tragedy: 1 / the presence of death; 2 / the authority of the rules; 3 / the expression of fate. Instead of a borderline tragedy, Bérénice may be said a model tragedy.